Evaluation of extraction-free RT-PCR methods for faster and cheaper detection of SARS-CoV-2 using two commercial systems. (November 2021) - Morecchiato, Fabio; Coppi, Marco; Baccani, Ilaria; Maggini, Niccolò; Ciccone, Nunziata; Antonelli, Alberto; Rossolini, Gian Maria
Highlights: Extraction-free methods allow faster and cheaper SARS-CoV-2 detection Extraction-free methods showed good sensitivity with samples with high viral load Heating step in extraction-free methods did not improve SARS-CoV-2 detection Abstract: Objective: When using high-throughput batched diagnostic platforms based on RT-PCR for SARS-CoV-2 detection, avoidance of the conventional nucleic acid extraction step can help to reduce the turnaround time and increase processivity. This approach can also spare reagents and plasticware, which have experienced a shortage during the initial waves of the pandemic, reducing the overall testing costs. Methods: This study evaluated the performance of extraction-free protocols based on simple dilution of the specimen in sterile RNAse free water (with or without a heating step) in comparison to standard RNA extraction protocols, using two commercial kits for molecular detection of SARS-CoV-2 (Allplex™ SARS-CoV-2 assay and Allplex™ SARS-CoV-2/FluA/FluB/RSV assay) in nasopharyngeal swabs (NPS). Results: Compared with conventional protocols, extraction-free protocols based on sample dilution without a heating step exhibited a lower analytical sensitivity: 74.0% and 82.1% with the Allplex™ SARS-CoV-2 assay (tested with 139 NPS samples) and the Allplex™ SARS-CoV-2/FluA/FluB/RSV assay (tested with 69 NPS samples), with a mean increase of Ct values of +2.04 and +1.32, respectively. Most false negative results were observed with sampled low viral load. Including a step of heat exposure did not improve but actually decreased the analytical sensitivity of the assay. Conclusions: Results confirmed that extraction-free protocols could be a faster and cheaper approach to SARS-CoV-2 detection in NPS samples, which could improve processivity of diagnostic platforms.